KONSEP PENDIDIKAN ANAK PRASEKOLAH PERSPEKTIF PSIKOLOGI PERKEMBANGAN DAN ISLAM - Samsudin, Mohamad; Haniefa, Rifda (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2023)
Children's education from the start is education with the greatest content and is an investment in the world of education in the future. Preschool education is one of the levels of education that plays a role in introducing the systematics of life in a directed way to a child with various patterns and formats. Therefore, philosophically, preschool education is not about learning something or getting to know new things. Preschool education actually prioritizes the formation of a child's orientation towards everything that requires processes and interactions with things that can naturally enrich their thinking.